Socialization of Strengthening the Integrity and Role of State Senior High School 14 Central Maluku in Fighting Corruption - Anwar, Arman; Ninkeula, Mareike; Manuputty, Gosalia Milka; Sabandar, Yonki (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Corruption is one of the biggest challenges for Indonesia, which is still being fought to be eliminated. Acts of corruption can not only damage the economic and legal order of the country, but more than that also damage the social and moral integrity of society.Purposes of The Devotion: To increase the awareness of State High School students of State High School 14 Central Maluku on the dangers of corruption and the importance of holding strong moral values in their daily lives in an effort to become agents to eradicate corruption from an early age both in the school environment, family, and the wider community. Method of The Devotion: It was carried out face-to-face with the resource persons in the classroom, and continued with an interactive discussion session where students were given the opportunity to ask questions related to corruption and its eradication efforts, and then explained again by the resource persons.Results Main Findings of the Devotion: Students of State High School 14 Central Maluku have become more aware of the importance of anti-corruption education as the basis for the formation of self-integrity and can know their role as Gen Z in eradicating corruption in all aspects of their lives. At their current critical age, where their moral values and integrity are beginning to take shape and their potential as learners that are still in the learning stage allows them to more easily accept and even apply the principles of honesty and accountability in their daily lives. The spirit of access to technology and communication through social media, which is very familiar to them, allows them to get information quickly and easily, and gives them the opportunity to be able to spread anti-corruption messages and increase public awareness at large and effectively. This certainly empowers students to become leaders with integrity, dare to speak out against corruption, and be able to create an environment that is free from corruption in the future.